Fresa, memorias y hombre nuevo. Sujeto e ideología en Gutiérrez Alea - Gustafsson, Jan (Diálogos Latinoamericanos, 2014)
The main aim of this article is to explore the relation between ideology and subject in the work of the Cuban film director, Tomás Gutiérrez Alea. The analysis will be based on two of his major works, Memorias del subdesarrollo (Memories of Underdevelopment), from 1968, and Fresa y chocolate (Strawberry and Chocolate), 1993. Special emphasis will be put on the socio-political context of these films, i.e. the Revolution and its utopiannationalist discourse and ideology as well as the consequences of this context for the individual and collective Cuban subject. Main conclusions of the analysis are that Alea’s criticism of the mechanisms of exclusion created by the Revolution is fundamental and, that it goes beyond the overt criticism of homophobic practices in Fresa y chocolate and of the bourgeois subject in Memorias. Alea, although positively engaged in the revolutionary process, demonstrates a capacity of fundamental social criticism and an essential ambiguity, in which the abyss between the individual subject and the totality of the Revolution is a central question.